2014
DOI: 10.1152/ajpendo.00436.2013
|View full text |Cite
|
Sign up to set email alerts
|

FFA-induced hepatic insulin resistance in vivo is mediated by PKCδ, NADPH oxidase, and oxidative stress

Abstract: Fat-induced hepatic insulin resistance plays a key role in the pathogenesis of type 2 diabetes in obese individuals. Although PKC and inflammatory pathways have been implicated in fat-induced hepatic insulin resistance, the sequence of events leading to impaired insulin signaling is unknown. We used Wistar rats to investigate whether PKCδ and oxidative stress play causal roles in this process and whether this occurs via IKKβ- and JNK-dependent pathways. Rats received a 7-h infusion of Intralipid plus heparin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
78
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 59 publications
7
78
1
1
Order By: Relevance
“…Studies of the effect of antioxidants on FFA-induced insulin resistance have generally not focused on the liver. We have reported that the pathway in the liver through which short-term plasma FFA elevation causes hepatic insulin resistance is as follows: protein kinase C delta (PKCd) activation/NADPH oxidase activation/oxidative stress/blunted insulin signaling (Pereira et al 2014). Taken together with the results shown herein, we can conclude that as the duration of plasma FFA elevation increases from 7 to 48 h, oxidative stress in the liver is normalized.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Studies of the effect of antioxidants on FFA-induced insulin resistance have generally not focused on the liver. We have reported that the pathway in the liver through which short-term plasma FFA elevation causes hepatic insulin resistance is as follows: protein kinase C delta (PKCd) activation/NADPH oxidase activation/oxidative stress/blunted insulin signaling (Pereira et al 2014). Taken together with the results shown herein, we can conclude that as the duration of plasma FFA elevation increases from 7 to 48 h, oxidative stress in the liver is normalized.…”
Section: Discussionsupporting
confidence: 76%
“…The underlying mechanism is unclear, but one possibility is that oxidative stress near the beginning of lipid infusion activates the transcription factor NRF2, which increases antioxidant enzyme expression (Cullinan & Diehl 2006), such that the oxidative stress is overcome by 48 h. Another potential explanation has hepatic PKCd as a key player. Both short-term (Pereira et al 2014) and prolonged (Pereira et al 2013) IH infusions lead to PKCd activation in the liver. Short-term IH infusion activates ERK1/2 in the liver (data unpublished) and it has been reported that PKCd activates ERK (Ueda et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saturated FFAs rapidly trigger generation of ROS, which may explain JNK activation. Mitochondria (34,35) and NADPH oxidase were discussed as predominant sources of palmitate-induced ROS generation in the liver (36,37). The FFA-induced JNK signal directs activated EGFR from proliferative signaling toward association with CD95 and proapoptotic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…One of the postulated mechanisms underlying obesityassociated insulin resistance and T2D is oxidative stress, which is defined as an excessive production of reactive oxygen species (ROS) (Matsuda and Shimomura, 2013). Accumulation of lipid within cells is always accompanied with over-production of ROS (Furukawa et al, 2004;Pereira et al, 2014). Treating obese mice with antioxidant agents could attenuate the development of diabetes (Kaneto et al, 1999).…”
mentioning
confidence: 99%